Rhodamine analogs for molecular ruler applications. (March 2016) - Chu, Yu-Hsuan; Escobedo, Jorge O.; Jiang, Meiyan; Steyger, Peter S.; Strongin, Robert M.
Abstract: A series of geometrically well-defined cationic fluorophores were designed based on molecular mechanics. They contain biaryl linkers to impart rigidity preventing intramolecular folding between a conjugated biomolecule and fluorophore. All probes have absorption and emission maxima within 20 nm from Texas Red, as predicted by TDDFT calculations and validated experimentally. Graphical abstract: Highlights: Extended rigid rhodamines were designed via molecular simulations. The trend of spectral properties of rhodamines agreed with TDDFT calculations. Amine-reactive probes for bioconjugation were synthesized. To be used as molecular ruler to study pore dilation in cationic channels.